Selfless intervention exercising jurisdiction in the common interest - Ryngaert, Cedric (Oxford, United Kingdom New York, NY, United States of America Oxford University Press, 2020)
Should states intervene in situations outside of their own territory in order to safeguard or promote the common good? In this book, Cedric Ryngaert addresses this key question, looking at how the international law of state jurisdiction can be harnessed to serve interests common to the international community. The author inquires how the purpose of the law of jurisdiction may shift from protecting national interests to furthering international concerns, such as those relating to the global environment and human rights. Such a shift is enabled by the instability of the notion of jurisdiction, as well as the interpretative ambiguity of the related notions of sovereignty and territoriality. There is no denying that, in the real world, 'selfless intervention' by states tends to combine with more insular considerations. This book argues, however, that such considerations do not necessarily detract from the legitimacy of unilateralism, but may precisely serve to trigger the exercise of jurisdiction in the common interest.
International Law and Cosmopolitanism -- Selfless Intervention: The Promise of Unilateral Jurisdiction -- Selfless Jurisdiction and the National Interest: Between Cosmopolitanism and Parochialism -- Limitations to the Exercise of Prescriptive Jurisdiction in the Common Interest -- The Selfless Exercise of Jurisdiction to Protect Human Rights and the Environment -- Concluding Observations.
Includes bibliographical references and index.
Keywords: Intervention (International law) -- Electronic books; Jurisdiction (International law); Intervention (International law); Jurisdiction (International law)